The effect of gold nanoparticles on the impedance of microcapsules visualized by scanning photo-induced impedance microscopy. (1st August 2016) - Wang, Jian; Campos, Inmaculada; Wu, Fan; Zhu, Jingyuan; Sukhorukov, Gleb B.; Palma, Matteo; Watkinson, Michael; Krause, Steffi
Abstract: Polyelectrolyte microcapsules have attracted great interest in drug delivery applications, and microcapsules modified with gold nanoparticles have been used in this way with triggered release when a laser can be used to remotely open shells through light-induced local heating. The electrical impedance of unmodified microcapsules has been studied due to its implications for their permeability, however, the impedance of functionalised microcapsules has not yet been investigated. Herein, the impedance of microcapsules modified with gold nanoparticles was studied for the first time. It was shown that the modification of microcapsules with gold nanoparticles leads to a much greater impedance than would be expected from the increase in the thickness caused by the presence of a layer of gold nanoparticles alone. The impedance of gold nanoparticle modified capsules was measured using scanning photo-induced impedance microscopy (SPIM), which is based on photocurrent measurements at an electrolyte-insulator-semiconductor (EIS) field-effect structure. High resolution and good sensitivity were achieved using a two-photon effect for charge carrier excitation and organic monolayer modified silicon-on-sapphire (SOS) as the SPIM substrate. SPIM allowed impedance imaging of collapsed microcapsules with unprecedented detail. SPIM images of capsules labelled with gold nanoparticles (AuNPs) showed a good agreement with the corresponding optical images, including the creases resulting from the collapse of the hollow shells. The significant increase in impedance caused by the impregnation with AuNPs was also verified by conductive Atomic Force Microscopy (C-AFM) measurements in the dry state.